2019
DOI: 10.3168/jds.2018-15417
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary phosphorus deprivation on leukocyte function in transition cows

Abstract: Phosphorus depletion and hypophosphatemia have been described to hamper immune function in different species, an effect barely studied in dairy cows commonly developing hypophosphatemia in early lactation. Dietary P deprivation in mid lactating dairy cows was associated with a decline of the number of granulocytes and impaired granulocyte survival, whereas the phagocytic activity remained unaffected. The objective of the study reported here was to determine the effect of P deprivation on the leukocyte function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…The positive effect of zeolite on blood calcium concentrations at calving is at least partially dependent upon lower plasma concentrations of phosphorus prepartum as additional prepartum supplementation with phosphorus interferes with the calcium response (Pallesen et al, 2008). Recent research also indicates that hypophosphatemia has a mild negative effect on granulocyte phagocytosis ability in transition dairy cows (Eisenberg et al, 2019). The clinical effects of short-term suppression of plasma phosphate remain unclear.…”
Section: Functionmentioning
confidence: 99%
“…The positive effect of zeolite on blood calcium concentrations at calving is at least partially dependent upon lower plasma concentrations of phosphorus prepartum as additional prepartum supplementation with phosphorus interferes with the calcium response (Pallesen et al, 2008). Recent research also indicates that hypophosphatemia has a mild negative effect on granulocyte phagocytosis ability in transition dairy cows (Eisenberg et al, 2019). The clinical effects of short-term suppression of plasma phosphate remain unclear.…”
Section: Functionmentioning
confidence: 99%
“…The consequences of SHC on health and reproduction have been widely studied worldwide, but those of SHP remain uncertain. Its detrimental effects on immunity have been demonstrated (Mullarky et al, 2009;Eisenberg et al, 2014;Eisenberg et al, 2019), but epidemiological studies quantifying the consequences regarding disease incidence and reproductive performance are lacking. Such studies are sorely needed to assess the need to take hypophosphatemia into consideration when implementing hypocalcemia prevention programs.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorus deficiency, especially around calving and in early lactation, has been associated with hampered productivity, feed intake depression and an increased risk of morbidity in fresh cows [ 27 ]. When investigating the immune system and resistance to infection, Eisenberg et al [ 28 ] stated that hypophosphatemia negatively affects both phagocytic activity and granulocyte count in transition Holstein dairy cows. However, in research conducted earlier by the same authors [ 29 ], granulocytes derived from cows fed a phosphorus-deficient diet were less viable, but phagocytic activity was not affected.…”
Section: Phosphorusmentioning
confidence: 99%
“…Reports on other animal species such as rats suggest that ATP content of leukocytes tends to be lower in hypophosphatemic individuals and that explains their decreased phagocytic activity and proliferation [ 31 ]. It is important to note that there are concerns regarding environmental pollution with P of fecal origin, thus it has been suggested that the P content of manure should be limited, thereby enforcing a more restrictive use of P in bovine nutrition [ 28 ].…”
Section: Phosphorusmentioning
confidence: 99%